Experimental investigation of a multi-stage impedance pumping system - Lee, Vincent; Abakr, Y.; Woo, K. (2012)
Impedance pumping is defined as a valveless pumping mechanism, where an elastic tube is joined with a tube of different impedance, a periodic asymmetrical compression on part of the elastic tube will produce a unidirectional flow. Numerical and experimental studies had been conducted in the past in the field of impedance pumping, but no work was found to exploit the principle of impedance pumping for the transportation of large amounts of fluids in industries. This piece of work describes the investigation of open-loop multi-stage valveless pumping experimentally. Computational Fluid Dynamics (CFD) simulations were done and proven the validity of impedance pumping in a large scale apparatus [12]. In this paper, demonstration of experimental setup will be discussed and results are presented. This investigation concentrates on the synchronization of pumping location as two actuators are implemented in the experiment and aims to generate a larger pressure head and net flow rate. Results showed that only at certain location along each tube that the pumping is optimum when being synchronized. Experimental results presented are significant and not previously presented, with a net flow rate obtained to be 40 times more than other available literatures thus far. © 2012 American Institute of Physics.